Hypochlorite-Activated Fluorescence Emission and Antibacterial Activities of Imidazole Derivatives for Biological Applications - Pham, Thanh Chung; Nguyen, Van-Nghia; Choi, Yeonghwan; Kim, Dongwon; Jung, Ok-Sang; Lee, Dong Joon; Kim, Hak Jun; Lee, Myung Won; Yoon, Juyoung; Kim, Hwan Myung; Lee, Songyi (Frontiers in Chemistry, 2021)
The ability to detect hypochlorite (HOCl/ClO-) in vivo is of great importance to identify and visualize infection. Here, we report the use of imidazoline-2-thiones (R1SR2) probes, which act to both sense ClO- and kill bacteria. The N2C=S moieties can recognize ClO- among various typical reactive oxygen species (ROS) and turn into imidazolium moieties (R1IR2) via desulfurization. This was observed through UV-vis absorption and fluorescence emission spectroscopy with high fluorescence emission quantum yield (ՓF = 43 - 99 %) and large Stokes shift (∆v ~ 115 nm). Furthermore, the DIM probe, which was prepared by treating the DSM probe with ClO-, also displayed antibacterial efficacy toward not only Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus) but also methicillin-resistant Staphylococcus aureus (MRSA) and extended-spectrum β-lactamase-producing Escherichia coli (ESBL-EC), i.e., antibiotic resistant bacteria. These results suggest that the DSM probe has great potential to carry out the dual roles of a fluorogenic probe and killer of bacteria.